Selective binding of choline by a phosphate-coordination-based triple helicate featuring an aromatic box - Jia, Chuandong; Zuo, Wei; Yang, Dong; Chen, Yanming; Cao, Liping; Custelcean, Radu; Hostaš, Jiří; Hobza, Pavel; Glaser, Robert; Wang, Yao-Yu; Yang, Xiao-Juan; Wu, Biao (Nature communications, 2017)
In nature, proteins have evolved sophisticated cavities tailored for capturing target guests selectively among competitors of similar size, shape, and charge. The fundamental principles guiding the molecular recognition, such as self-assembly and complementarity, have inspired the development of biomimetic receptors. In the current work, we report a self-assembled triple anion helicate (host 2) featuring a cavity resembling that of the choline-binding protein ChoX, as revealed by crystal and density functional theory (DFT)-optimized structures, which binds choline in a unique dual-site-binding mode. This similarity in structure leads to a similarly high selectivity of host 2 for choline over its derivatives, as demonstrated by the NMR and fluorescence competition experiments. Furthermore, host 2 is able to act as a fluorescence displacement sensor for discriminating choline, acetylcholine, L-carnitine, and glycine betaine effectively.The choline-binding protein ChoX exhibits a synergistic dual-site binding mode that allows it to discriminate choline over structural analogues. Here, the authors design a biomimetic triple anion helicate receptor whose selectivity for choline arises from a similar binding mechanism.
Keywords: vazba proteinů; Proton Magnetic Resonance Spectroscopy; Carrier Proteins; Acetylcholine; acetylcholin; transportní proteiny; fosfáty; membránové transportní proteiny; Protein Binding; Kinetics; Choline; Membrane Transport Proteins; Binding Sites; kinetika; Bacterial Proteins; Protein Domains; Phosphates; krystalografie rentgenová; bakteriální proteiny; Binding, Competitive; protonová magnetická rezonanční spektroskopie; Crystallography, X-Ray; molekulární modely; vazebná místa; proteinové domény; kompetitivní vazba; Sinorhizobium meliloti; Models, Molecular; cholin